The Strategic Alliance in 5G Development in Taiwan: A Resource-based Approach - Wen-Yi Hsu (International Telecommunications Society (ITS), 2020)
The 5G spectrum bidding was finalized, and the total 5G bid had hit a sky-high of NT 142.191 billion ( 4748.33million). In the month of July, it is expected that there will be two telecom operators launching the 5G services, which is where the 5G era begins in Taiwan. Following Chunghwa Telecom and Far Eastern Telecom, the mobile broadband service security maintenance plan proposed by Taiwan Mobile has also been approved by the NCC on May 6, 2020. Taiwan Mobile is very active in cooperating with other players, including promoting the "5G Super Alliance" using the resource advantages available in the telecommunications industry, which allows cross-domain and cross-country alliance cooperation along with various leadership styles from different fields together with modern operation planning. In Taiwan, there is very few research about evaluating or selecting strategic alliance partners of telecommunications companies in the next generation network era. Taiwan Mobile's core resources and capabilities are different from those of other telecom operators. This research conducts a case study on Taiwan Mobile, using resource-based theory of strategic alliances to analyze its current status of 5G application service operations, "core resources" and 5G application service "strategic alliances" and other planning and development, exploring how Taiwan Mobile establishes its advantages and characteristics to develop its business strategy. Taiwan Mobile's "5G Super Alliance" gathers nearly 100 top teams in the three areas of production, government and research. Taiwan Mobile mainly forms a 5G application development strategic alliance in the form of functional agreements, joint research and development, and diversified integration. However, even with ambitious aspiration for the 5G technology, the real challenge of "network construction" in Taiwan's development of the 5G industry has only just begun.
Keywords: 330; 5G networks; complementary resources; resource-based theory of strategic alliances; spectrum bidding